Fetal brain ultrasound measures and maternal nutrition: A feasibility study in Ecuador. Issue 2 (16th August 2020) - Sibbald, Carrie A.; Nicholas, Jennifer L.; Chapnick, Melissa; Ross, Naima; Gandor, Patricia L.; Waters, William F.; Palacios, Iván; Iannotti, Lora L.
Abstract: Objective: Nutrition during pregnancy is an important modifiable determinant of fetal growth and development. This pilot study aimed to characterize the association between fetal anthropometry, fetal brain development, and maternal diet among women in Ecuador using portable ultrasound in resource‐limited clinics, including measurements of brain structures not typically imaged in this setting. Methods: Pregnant women (n = 47) from four resource‐limited health centers were surveyed on demographic, socioeconomic, morbidity, and dietary information. Maternal height, weight, and blood pressure were taken. A sonographer took 15 images per participant, including those standardly assessed during the fetal survey and additional brain structures identified as potentially responsive to maternal nutrition, but not part of the standard fetal survey. Results: Mean percentiles for all standard fetal survey measurements generated from WHO Fetal Growth Curves fell below 50%, and negative mean Z scores were found for biparietal diameter (−0.95 ± 1.11) and femur length (−0.22 ± 1.10). Generalized linear modeling adjusting for gestational age and other covariates showed frequency of seafood consumption was positively associated with fetal biparietal diameter Z score ( P = 0.005), beans and legumes positively associated with femur length ( P = 0.006), and a negative association was found for soda consumption and fetal head circumference ( P = 0.013). Conclusions: This pilot study demonstrated the feasibility of capturing images of nutrition‐relevant fetal brain structures not part of the standard fetal survey in resource‐limited settings using portable ultrasound. Our study revealed associations between anthropometry, brain structure size, and maternal diet demonstrating potential for prenatal nutrition research using ultrasound in the field.